PEMBESARAN UDANG GALAH (Macrobrachium rosenbergii de Man) DENGAN SISTEM MONOSEKS DAN CAMPURAN TERHADAP PERTUMBUHAN, KELANGSUNGAN HIDUP, DAN FCR - Derri Syatriawan; Indah Anggraini Yusanti; Syaeful Anwar (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2019)
Giant Freshwater Prawns (Macrobrachium rosenbergii de Man) is a potential freshwater fishery commodity for commercial cultivation. Rapid growth, large size, low prevalence of diseases and widespread market demand, both domestic and export markets, are potentials that make these commodities play an important role in freshwater fisheries business in Indonesia. The purpose of this research is to know growth, survival, conversion of Giant Freshwater Prawnsfeed (Macrobrachium rosenbergi de Man) on monosex and mixed cultivation systems. This research was conducted for three months from September to November 2017. In Installation of Giant Freshwater Prawn Hatchery (IPUG) Central Freshwater Aquaculture (BBPBAT) in Sukabumi, Cisolok KarangPapak, PelabuhanRatu, Sukabumi, West Java. The research method is experimental using Completely Randomized Design (RAL). In this research, there are three treatments and three replications, namely the maintenance of prawns in research containers based on male sex. Treatment P1 (100% male), P2 (100% female), and P3 (mixture of 50% male and 50%  female). The results of this research showed that best total growth and weight were shown by treatment P1 namely of 3.85 cm and 14.62 gram. The best survival rate (SR) was 76.67%in treatment P2, and the best feed conversion (FCR) was 2.50 intreatment P3. The statistical test results showed that H0was accepted and H1was rejected for all treatments. Keywords : Giant Freshwater Prawns, Growth, Survival, FCR